3D virtual worlds in education and training - Sampson, Demetrios (2011)
This paper presents education and training using virtual reality. Today, the emergence of technologies, such as 3D Virtual Worlds (VWs), which provide realistic three-dimensional environments and offer engaging, interactive and immersive experiences, creates new opportunities for teaching and learning. These opportunities are related to the faithfulness of the educational activities representation within 3D VWs and also to the enhanced aspects of interactivity provided within them.